Issues of Disagreement and the Treasury of Islamic Knowledge - Miftahurrizki, Miftahurrizki; Ardiansyah, Deni; Ghazali, M. Bahri (Westscience Press, 2025)
Khilafiyah, or differences of opinion in Islam, is an inherent phenomenon in the history of Islamic thought. This study aims to explore the dynamics of khilafiyah and its contributions to enriching the Islamic intellectual tradition. Using a qualitative approach based on literature review, this research examines classical and contemporary sources to identify the causes of differences of opinion, the methodological frameworks of scholars, and the relevance of khilafiyah in addressing modern issues. Findings indicate that khilafiyah not only broadens the intellectual horizons of Muslims but also serves as a crucial foundation for the development of disciplines such as fiqh, usul fiqh, hadith studies, and theology. Amidst the challenges of globalization and pluralism, khilafiyah remains relevant as an adaptive and solution-oriented tool for contextual ijtihad. However, critical awareness is needed to prevent polarization of the ummah due to the misuse of differences. Thus, khilafiyah must be understood as an intellectual heritage that reinforces the values of moderation, tolerance, and diversity within the framework of ummah unity.